De la police coloniale française à la police nationale marocaine : décolonisation et héritages policiers (1953-1960) - Benjamin Badier (L’Année du Maghreb)
Among the numerous institutional continuities between the French protectorate over the Cherifian Empire (1912-1956) and independent Morocco, the security forces, particularly the police, stand out. The General Directorate for National Security (DGSN), which remains at the core of the police apparatus to this day, was not created from scratch in 1956, but rather evolved from the Cherifian Police, the protectorate institution controlled by the French. The police continuities, which unfold across various institutional, doctrinal, and human levels, seem astonishing, given the central role the Cherifian Police played in maintaining colonial order and harshly repression independence movements.This article delves into the institutional history of the police in Morocco from August 1953, when the exile of Sultan Mohammed V triggered a wave of nationalist violence that severely tested the colonial police, to the year 1960, when the privileged connection with France was questioned by the Moroccan regime on all fronts, including within the police. Like the history of the police during the protectorate, the history of the Moroccan police during decolonization and after independence remains to be written. French diplomatic archives enable the reconstruction of the general institutional framework of the police during the protectorate, as well as after independence – precisely due to these continuities. While the archives of the DGSN are not available, those of the Consultative National Assembly (1956-1959), held at the Archives of Morocco, provide valuable insights, along with the critical perspective of the Moroccan left. The first part examines the transformations of the Cherifian Police in the early 1950s, when it struggled to reorganize itself to confront the increasingly violent nationalist mobilizations. Established in 1913, the Cherifian Police was conceived as a state police force with jurisdiction across the entire territory of the French zone of the protectorate. While by the 1930s its mission was to combat nationalism, surveillance and repression of Moroccan political parties became its main focus after the war. Undergoing several reforms and modeling itself after the metropolitan police, the colonial police became increasingly centralized and specialized in intelligence. However, it consistently suffered from understaffing, struggled to fulfill its assigned tasks, and faced rivalry with the French army, a central actor in colonial policing. The organization and tasks of the Cherifian Police discard a hypothesis that could have explained the post-colonial institutional continuity. This continuity owes little to the principle of indirect rule on which the protectorate is based, or to the French project of reforming the Moroccan state. The Cherifian Police is a mixed institution, with one-third of its personnel being Moroccan agents; the maintenance of order similarly relies on pre-colonial institutions, such as the assès and the mokhazni. However, the idea of a potential transfer is by no means the cause of this composite nature, which is rather explained by the necessity of maintaining order, the need for colonial intermediaries, and the limited French resources.The strong continuity between the French colonial police and the Moroccan national police is actually to be explained by the specific context of power transition between colonial authorities and the Moroccan palace after the fall of 1955. This context is one of heightened security deterioration and a renewed alliance between the monarchy and the French, as the latter recall the sultan from exile and pave the way for independence (March 1956). The shared interest of these actors is to establish a strong monarchical regime in the country to counter the nationalists (particularly the Istiqlal Party) and their aspiration for governance. This leads to an institutional transfer, especially of the police forces specialized in combating nationalism. The DGSN, established at that time, reports to the Palace rather than the Ministry of the Interior. It inherits the structures of the Cherifian Police, and many French police officers remain in the Moroccan national police as collaborators (one-third of the personnel in 1957). There is indeed a process of Morocconization of the police, but it is gradual. The true turning point occurs in 1960 when Morocco questions its privileged ties with France. The expulsion of the last French police agents coincides with an authoritarian shift against the Moroccan left, which denounces a police regime inherited from the colonial era.